COMMUNICATION STYLE AND SELF PRESENTATION OF @DokterDetektif IN EDUCATIONAL CONTENT ON TIKTOK MEDIA - ramadhini, Syafira andzani; Kumalasari, Astini; Mardiana, Lisa (Jurnal Visi Komunikasi, 2025)
The communication style of a KOL, Detective Doctor is able to create informative and interesting content, starting from a TikTok account that has its own characteristics, to the content that makes it known to the wider community. In the context of verbal communication, the message conveyed by Detective Doctor through social media content is expressed in the form of certain words or sentences that reflect the characteristics of his communication style. The aim is to find and understand the communication style of detective doctors in reviewing skincare products. This research applies a qualitative method with a descriptive approach. This study uses the theory of communication style and self-presentation. primary data through non-participant observation by observing the TikTok account @dotif and reviewing the content of the detective doctor who reviews products. The results of this study concluded that there are four communication styles used by detective doctors to create success in their communication. and one element of self-presentation that is consistently used by detective doctors.